Cutaneous larva migrans in a 4-month-old child. - Hunashikatti, V.B. (European Journal of Pediatric Dermatology, 2025)
Cutaneous larva migrans (CLM) is a skin infestation caused by a nematode larva, Ancylostoma brasiliensis. The infective larvae hatched from parasite eggs enter human skin when encountered with infested soil. Linear erythematous itchy lesions occur along the path of the larva within skin. Generally seen between 2-5 years of age with peak incidence around 5-14 years, it rarely occurs in early infancy. And here we report one such case affected at 4 months of age.